Estimating Quarterly GDP for Nepal: An Application of Chow-Lin Procedure - Adhikari, Naveen; Nepal, Tulasi (Economic Journal of Nepal, 2019)
Nepal started producing annual national income estimates following an internationally accepted system of ’National Account Systems’ since the late1960s; and, accordingly, the annual GDP figures for Nepal are available for a longer period. However, the production and publication of quarterly GDP for public consumption have been both rare and occasional. This paper aims to bridge this gap by providing an estimate for quarterly GDP for the period of 1997/98 Q1 to 2017/18 Q4 following well established Chow-Lin procedure. The quarterly exports and government tax revenue are used to extrapolate the magnitude and movement of quarterly GDP. The results show a deterministic seasonal movement over the quarters. In particular, increased economic activities are observed in the second and fourth quarters while making a comparison on quarter to quarter basis. It is expected that this paper will partially fulfill the gap of unavailability of quarterly GDP figures in the public domain, and documents that the researcher may use suitable econometric exercise to obtain inter-temporal disaggregation of low-frequency data such as annual GDP into quarterly figures.